Accelerometry and Self-report in Sedentary Populations - Jovanovic, Jennifer L. (2011)
OBJECTIVES: To determine whether self-reported exercise duration and intensity matched accelerometer data in sedentary endometrial cancer survivors and age-matched controls. METHODS: Participants were asked to wear an accelerometer and self-report exercise bouts, duration, and intensity for one week. Self-reported duration was compared with accelerometer data. RESULTS: Self-reported exercise-bout duration matched accelerometer duration 93% for survivors and 99% for controls. Self-reported exercise-bout intensity matched accelerometer intensity 70% for survivors and 66% for controls. There were no significant differences between groups. CONCLUSIONS: Sedentary endometrial cancer survivors and controls self-reported duration and intensity of physical activity consistent with accelerometer data.